5.2_summation_formulas-1

5.2_summation_formulas-1 - + 1 2 n 2 + 1 6 n n X k =1 k 3 =...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Summation Rules n X k =1 ( a k + b k ) = n X k =1 a k + n X k =1 b k n X k =1 ( ca k ) = c n X k =1 a k , for any constant c n X k =1 a k = K X k =1 a k + n X k = K +1 a k , for integers 1 K n - 1 . Common Sums n X k =1 1 = n n X k =1 k = n ( n + 1) 2 = 1 2 n 2 + 1 2 n n X k =1 k 2 = n ( n + 1)(2 n + 1) 6 = 1 3 n 3
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: + 1 2 n 2 + 1 6 n n X k =1 k 3 = n 2 ( n + 1) 2 4 = 1 4 n 4 + 1 2 n 3 + 1 4 n 2...
View Full Document

Ask a homework question - tutors are online